HUBUNGAN PHUBBING SMOMBIE DAN NOMOPHOBIA TERHADAP PERILAKU MANUSIA - Resha Khofila; Muhammad Putra Dinata Saragi; M Alif Erhanda Lubis; Fildzah Ghaisani (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
The use of gadgets that are not wise and proportional has caused a person's social, mental, and medical problems. Phubbing and smombies are one of the impacts of this problem. Phubbing stands for phone snubbing which refers to the behavior of people who are more focused on using gadgets than interacting with people or the environment around them. Smombie is a person who constantly uses a smartphone, cellphone, or gadget while walking. Or pedestrians who focus on their cellphones without paying attention to their surroundings. While Nomophobia refers to "anxiety about not having access to cell phones or cell phone services. Human behavior is essentially a process of individual interaction with the environment as a biological manifestation that he is a living being.  The behavior of someone who is exposed to phubbing, smombie, or nomophobia is the result of a response to the behavior of those who have been in the habit of using smartphones since childhood. Phubbing, smombie, and nomophobia greatly affect the life of everyone who experiences it such as safety, mental health, social interaction with other people, a person can be affected by this excessive use of cellphones.